Pinch your pottery : the art & craft of making pinch pots : 35 beautiful projects to hand-form from clay - Atkin, Jacqui (Quarto Publishing, 2021)
"Pinching is a wonderfully direct method of interacting with clay, capable of making a myriad of forms, usually small, and requiring the minimum of tools. With this superb collection of pinched projects, Jacqui Atkin, a widely respected ceramics teacher and author, shows what this simple technique is able to achieve. Each project is explained with step-by-step sequences and plenty of options for surface decoration and glazing techniques. There's something to suit all making preferences, from the functional to the purely decorative, including imaginative sculptural works."-From back cover.